The Arab Spring: challenges to the US Middle East policy - Ra'ees, Wahabuddin (Inderscience Enterprises Ltd., 2012)
This study argues that the Arab World and the larger Middle East region are politically, strategically, and economically significant in the US foreign policy formulation. However, the 2011 Arab Spring poses serious challenges to Washington’s interests and policy in the region. The Arab Spring entails political elite transformation in the Arab countries of the Middle East region. The Arab Spring could sweep into power the Arab nationalists and the Islamists. In the democratic Middle East, the effectiveness of the State of Israel card as the only democratic state will diminish. The study concludes that unless Washington in search of new allies adopts the approach of constructive engagement and inclusive democracy in the larger Middle East region, Iran will exploit the Arab street protests and thwart USA’s interests and stability in the region.